Pectoralis Major Muscle Belly Repair in a Young Male Adult: A Case Report. Issue 1 (January 2021) - DeRogatis, Michael J.; Kelly, Sean C.; Hanflik, Andrew M.; Pae, Robert; Sieczka, Elizabeth M.; Issack, Paul S.
Abstract : Case: A 29-year-old man sustained a near-complete laceration to the left pectoralis major muscle belly. The muscle and epimysium were repaired using the Kragh technique—a combination of running interlocked and Mason-Allen stitches. At the 6-year follow-up, the patient had an excellent outcome as measured by clinical scores (Short Form Survey-36, Disabilities of the Arm, Shoulder, and Hand, and American Shoulder and Elbow Surgeons Score), bench press, cosmesis, and magnetic resonance imaging. Conclusions: Acute traumatic open pectoralis muscle belly tears may be successfully repaired in select patients using the Kragh technique with excellent postoperative function and cosmesis.